P531 Chemsex and STI clinic use among MSM: results from a large online survey in england. (14th July 2019) - Blomquist, Paula; Mohammed, Hamish; Mikhail, Amy; Weatherburn, Peter; Reid, David; Wayal, Sonali; Hughes, Gwenda; Mercer, Catherine
Abstract : Background: Chemsex, the use of select psychoactive drugs to enhance sexual experience, typically among men who have sex with men (MSM), is associated with STI risk behaviours. Understanding characteristics of MSM who engage in chemsex and their use of STI clinics is important for developing interventions. Methods: Between 5/2016-5/2017, 3, 358 MSM (aged≥15years; no known HIV infection) completed an online survey, largely via 4 gay social-networking apps. We described patterns of chemsex and differences in demographics, awareness of 8 common STIs, STI risk behaviour, and STI clinic attendance between those engaging in chemsex and those not. We used a composite measure 'high STI risk' comprising condomless anal sex (CAS) with ≥11 men/past 3m, of whom ≥1 had unknown HIV status. We used logistic regression to investigate the association between chemsex and clinic use/past 3m. Results: 8% of respondents reported chemsex/past year. Among them, 70% had used ≥2 different chemsex drugs, with mephedrone (68%) most popular. A greater proportion of MSM who reported chemsex, compared to those who did not, were university graduates (63% vs 52%), <40years (51% vs 43%), aware of all 8 asked-about STIs (34% vs 22%), reported CAS/past 3m (73% vs 47%), and were classified as 'high STI risk' (26% vs 8%). MSM who reported chemsex were more likely to have attended an STI clinic/past 3m vs those who did not (63% vs 34%), including after controlling for sociodemographics: adjusted odds ratio: 2.97, 95%CI: 2.26–3.90. Of those at 'high STI risk' (n=317), 75% of MSM reporting chemsex, vs 48% of those not, had been to clinic/past 3m. Conclusion: A minority of MSM engage in chemsex. Those that do appear to be at greater STI risk but engage more actively with STI clinics. More targeted STI prevention efforts are needed to improve access to clinical services for all MSM at high risk of STIs. Disclosure: No significant relationships.